BORNEO FINE ART GALLERY DI KOTA PONTIANAK - Habibie, Caesar Nakula Rafi; Affrilyno, Affrilyno; Purnomo, Yudi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
The development of art, especially illustration, has been a much-discussed topic among Indonesians, both young and old. Fine art emphasises on freedom of expression, aesthetics, and also about conveying deep messages and encouraging reflection, including painting, sculpture, graphics, photography, and digital art. One of the issues in Pontianak City is the absence of a special building or space that meets the standards of fine art exhibition. The design method is based on Archer (1968), namely programming (determining important issues), data collection (classifying and storing data), analysis (reassessing the proposed programmed and estimating), synthesis (initial concept development), development (outline concept mapping), and communication (final presentation). By considering the environmental, and geographical aspects of Pontianak City. The selection of the main theme in the design of Borneo Fine Art Gallery in Pontianak City is